Disasters in Japan: LIASE-Funded On-site Experiential Learning Courses Exploring the Science, Social Impact, and Culture of Disaster. Issue 2 (31st December 2019) - Bates, Alex
Abstract : This article describes two interdisciplinary summer experiential learning courses focused on disasters in Japan, both partially funded through LIASE (Luce Initiative on Asian Studies and the Environment). The first course was titled "Seismic Japan" and was centered on earthquakes through Japan's history culminating in the 2011 disaster. The second, "Meltdowns and Waves, " was a comparative look at the Three-Mile Island meltdown incident, the Fukushima Daiichi nuclear disaster, Hurricane Sandy, and the 2011 tsunami. Both courses provided a unique interdisciplinary learning experience for our students, one that explored the science behind earthquakes, tsunamis, and nuclear accidents as well as the impacts of these disasters on Japanese society and culture.